Denture Hygiene: The Sharing Responsibility - Zakaria, Wael; Almunajem, Yasser; Alnowaiser, Hadeel (International Journal of Dental Research, 2018)
Background: Regular and effective denture hygiene among complete denture patients has a great effect on preventing various oral lesions based on appropriate hygiene measures given by the prosthodontist. Objective: The current study aimed to analyze the denture hygiene behaviors among complete denture wearers at the Dental Hospital in Qassim University, KSA. Subjects and Methods: In the current study, 91 complete denture wearers (61 males and 30 females) attending the dental clinics at Qassim University in Saudi Arabia were included. A questionnaire was used which mainly focuses on evaluating the participants regarding the complete denture hygiene and their behaviors and ability to clean the denture at appropriate intervals.Results: A total of 91 patients were interviewed. Their age ranges between 35 to 85 years. (92.3%) of the participants received instructions about cleaning and care of their denture.78% of these instructions were verbal. (51.6%) of complete denture wearers used water and a toothbrush to clean their denture. Most of the patients (76.62%) removed their denture at night before sleep while less number (26.37%) did not. With regard to routine follow up, 73.6% of participants never attend any visit.Conclusion: Improve the awareness of complete denture patients towards the importance of maintaining their denture hygiene and the importance of regular periodic visit is a sharing responsibility between the prosthodontist and the patients.